Assessment of predictors of unskilled delivery among women seeking immunization services in Kitui County, Kenya - Mbuthia, Zipporah W.; Kariuki, John G.; Kerochi, Atei (International Journal Of Community Medicine And Public Health, 2023)
Background: Globally, maternal mortality was the second leading cause of mortality among women of reproductive age in 2016 after HIV/AIDS. In 2017, global and Africa maternal mortality rate (MMR) was 211 and 547 maternal deaths per 100,000 live births respectfully. Unskilled delivery is one of the underlying causes of maternal mortality. Methods: The study assessed the predictors of unskilled delivery among women in Kitui County, Kenya. The facility-based study was cross-sectional with mixed method of data collection. Facilities were selected through simple random sampling and systematic sampling for participants. A structured questionnaire was administered among 380 women seeking immunization services and analysed using Stata. Twelve key informant interviews were conducted and analysed thematically. Results: The level of unskilled delivery was 29.21%. On inferential analysis income [p=0.023], education [p=0.002], ANC visits [p=0.014], birth preparedness (BP) [p=0.042] and maternal complications [p=0.027], time taken to health facility [p=0.030] and quality of care [p=0.001] were statistically associated with unskilled delivery, p<0.05, C.I.=95%. On logistic regression low income (AOR=4.8356), low education (AOR=4.3169), few ANC visits [aOR=2.6444], lack of BP [aOR=5.0499], history of maternal and child complications [aOR=6.0237], longer time to health facility [aOR=0.1652] and poor quality of care [aOR=0.5615] were positively associated with unskilled delivery. Conclusions: The level of unskilled delivery in Kitui county was 29.21%. Predictors of UBA were low income, low education, fewer ANC visits, lack of BP, history of maternal and child complications, longer time to health facility and poor quality of care.